The Role of Acupuncture and Stem Cell Therapy in Enhancing Stroke Recovery - Dimara, Imelda; Barasila, Atikah Chalida (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2024)
Stroke is an acute neurological disorder caused by disrupted blood flow to the brain, depriving cells of oxygen. From 1990 to 2019, it was the world’s second-leading cause of death and the third-leading cause of combined death and disability. Acupuncture plays a role in stem cell treatment by activating the body's natural recovery processes through physical stimulation, aiding the recovery and rehabilitation of stroke patients. Several studies have explored combining stem cell therapy with acupuncture, yielding promising results in improving patient outcomes. This review assesses the effectiveness of combining acupuncture with stem cell therapy for stroke recovery. Analysis of seven randomized controlled trials shows that both stem cell transplantation and acupuncture contribute to the rehabilitation of stroke patients. When applied together, this combined therapy improves the survival, retention, and functional differentiation of implanted stem cells, creating a synergistic effect that amplifies the benefits of each treatment and compensates for their individual limitations. Key acupuncture points for this combination therapy include GV20, GV14, LI11, ST36, and GV26, with treatment durations ranging from 10 to 22 days.